Roadmap to the Mechanisms of Aortic Regurgitation on Echocardiography - Addetia, Karima (JACC Case Rep, 2020)
The purpose of this series was to improve assessment of the aortic valve by echocardiography and to encourage echocardiographers to assess the cause of aortic regurgitation. The study illustrates the use of the Carpentier classification system for classifying the causes of regurgitation with a case series. (Level of Difficulty: Intermediate.)